Analisis Dan Perancangan Sistem Pendukung Keputusan Pemilihan Pendamping Sosial Terbaik Program Keluarga Harapan Dengan Metode SAW Pada Dinas Sosial Kota Jambi - Treseli, Nerviana; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2021)
The selection of the best social companion of Conditional Cash Transfers (CCT) at the Social Service Office in Jambi City is a reward given to stimulate enthusiasm in increasing the dedication and performance of the companion in the field, but the selection decision has not been measured with data, therefore a decision support system is needed in making decisions. The purpose of this study was to analyze and design a decision support system for selecting the best social assistant of Conditional Cash Transfers (CCT) with the SAW Method in the Jambi City Social Service. Software used in the design are Balsamiq Mockups 3, StarUML and Microsoft Office. In the Decision Support System there are various methods. At the moment there are 78 Family of Social Assistance Program assistants whose assisted locations are spread throughout the Jambi city. With this research, it is expected that later it can help decision makers in determining the best social companion Family Program expectations in the Jambi City Social Service.